2016
DOI: 10.1177/0263276416667197
|View full text |Cite
|
Sign up to set email alerts
|

Africa’s ‘Two Publics’: Colonialism and Governmentality

Abstract: In this article, I explore a possible ‘conversation’ between a leading African political sociologist, Peter P. Ekeh, in his theory of ‘two publics’, and the late French philosopher, historian and social theorist, Michel Foucault, in his theory of governmentality. I examine the ‘lingering effects of colonialism’ and point to how Ekeh’s insight and its usefulness for examining the politico-cultural consequences of colonialism in terms of the conduct of conduct in the public realm can be further enriched by relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In a move that coincides with Mbembe's (2002) minimisation of the effects of colonialism on Africa, some scholars point to pre-colonial processes to explain the convergence and overlap between the civic and primordial spheres (Bayart 1993; Joseph 1997). Another explanation subscribes to the thought that colonialism had drastic effects on Africa (Osaghae 1994; Mamdani 1996; Taiwo 2010) in asserting that the primordial public, contrary to the thought of Ekeh, was also significantly shaped by colonialism (Osaghae 2006: 241; Adebanwi 2016: 13). The colonial state was often directly involved in carving out ethnic territories, getting groups of people to think of themselves as ethnic groups and distributing rights, privileges and responsibilities within these groups (Iliffe 1979; Ranger 1983; Mamdani 1996; Ndegwa 1997: 601; Berman 1998: 313–15; Adejumobi 2001: 157; Lynch 2006; Onoma 2010; Taiwo 2010).…”
Section: Ebola Ekeh's Two Publics and The Negotiation Of Contested Tiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In a move that coincides with Mbembe's (2002) minimisation of the effects of colonialism on Africa, some scholars point to pre-colonial processes to explain the convergence and overlap between the civic and primordial spheres (Bayart 1993; Joseph 1997). Another explanation subscribes to the thought that colonialism had drastic effects on Africa (Osaghae 1994; Mamdani 1996; Taiwo 2010) in asserting that the primordial public, contrary to the thought of Ekeh, was also significantly shaped by colonialism (Osaghae 2006: 241; Adebanwi 2016: 13). The colonial state was often directly involved in carving out ethnic territories, getting groups of people to think of themselves as ethnic groups and distributing rights, privileges and responsibilities within these groups (Iliffe 1979; Ranger 1983; Mamdani 1996; Ndegwa 1997: 601; Berman 1998: 313–15; Adejumobi 2001: 157; Lynch 2006; Onoma 2010; Taiwo 2010).…”
Section: Ebola Ekeh's Two Publics and The Negotiation Of Contested Tiesmentioning
confidence: 98%
“…The theory's parsimony, its historicising of processes and entities that some tend to reify and its effort to grapple with some of the most important dynamics in post-colonial Africa explain its enduring influence on a wide set of literatures on contemporary Africa (Bratton 1989; Ibrahim 1991; Fowler 1993; Joseph 1997; Ndegwa 1997; de Sardan 1999; Adejumobi 2001; Englebert 2002; Obadare 2005; Erdmann & Engel 2007; Osaghae 2007; Adebanwi 2016). It tends to ground and legitimise certain ways of seeing and writing about Africa that emphasise state-society chasms, the conflict-ridden nature of inter-communal relations and the moral and benign character of intra-(primordial) group relations (Ake 1985; Lewis 1992; Osaghae 1995; Berman 1998; de Sardan 1999; Igwara 2001; Ukiwo 2005).…”
Section: Ebola Ekeh's Two Publics and The Negotiation Of Contested Tiesmentioning
confidence: 99%
“…For the appointed resource managers, who are foreign expatriates, every allusion to the development agenda in Jogbo, in ways representative of the Nigerian oil exploration and its wealth management is constantly and patently disregarded and circumvented. In many respect, the movies captured what scholars on governance studies have found about the Nigerian oil state (Joseph, 1999;Obadare & Adebanwi, 2010;Adebanwi, 2017). Evidences that democratic states have stronger tendencies to continually improve on the welfare of the citizens than autocratic regimes (Charron & Lapuente, 2009;Gjerløw, Knutsen, Wig, & Wilson, 2018)) also featured prominently in the movies.…”
Section: Analysis and Discussionmentioning
confidence: 78%
“…Casting the language of the play in standard Yoruba language with cutting-edge English subtitles, Kelani reached into the political attitude arguably prevalent in Nigeria and generally found to be encountering fundamental political condescending (Joseph, 1999;Obadare & Adebanwi, 2010;Adebanwi, 2017), and approaching state failure (Soyinka, 1996;Maier, 2000;Collier, 2008). The movies genially and firmly storied a political conversation with a larger audience than any other works of its time (Haynes, 2007quoted in Balogun, 2018 using proverbial devices (Ayodabo, 2016); adaptation of poetic devices to unravel memory (Balogun, 2018); "agenda of transformation" and emergence from crisis (Onikoyi, 2016:242).…”
Section: Contextual Settings Of Allegorical Statehood In Saworoide Anmentioning
confidence: 99%
“…Contemporary accounts of liberal government rely upon varying and diverse genealogies through encounters with postcolonial studies (Agathangelou, 2013; Kapoor, 2013; Richter-Montpetit, 2014; Wynne-Hughes, 2015). However, the most extensive of these engagements have taken place outside of IR (Adebanwi, 2017; Chow, 2002; Legg, 2014; McIntyre and Nast, 2011; Povinelli, 2011; Scott, 1999; Stoler, 1995, 2016; Venn, 2009). Despite the emergence of work examining IR’s neglect of racism and colonialism (Anievas et al, 2014; Bell, 2013; Carrozza et al, 2017; Rutazibwa, 2016; Shilliam, 2013) and the push to engage postcolonial and decolonial scholars in the critique of war, humanitarianism and development (Barkawi, 2016; Sabaratnam, 2017; Sajed, 2013), there still remains a tendency for scholars of European states to overlook the place of colonialism in the development of contemporary rule and the production of modern racism (see Venn, 2009).…”
Section: Introductionmentioning
confidence: 99%